Preparation of a small-size superconducting joint for C-doped 30-filament MgB2 wires. (29th October 2021) - Xi, Dan; Wang, Dayou; Xinwei, Cai; Wang, Qingyang; Huang, Zigeng; Nie, Ruijuan; Yan, Guo; Wang, Furen; Gan, Zizhao
Abstract: A preparation method of a small-size MgB2 superconducting joint with 2.0 mm diameter for C-doped 30-filament MgB2 wires is presented in this paper. Herein, an unreacted in situ C-doped monofilament wire was utilized as the connecting structure, since it contains a low quantity of dense precursor which needs less pressure during fabrication, avoiding distortion of the multifilament in the parent wires, as shown in SEM images. After heat treatment, the formed C-doped MgB2 bulk with small volume in the joint has the ability to release heat quickly, resulting in good stability. The morphology of the joint proved the MgB2 –MgB2 interface between the monofilament and 30-filament wire had been successfully connected. The joint sintered at 600 °C for 2 h shows an apparent superconducting transition with T c-on = 33.49 K and has negligible resistance below 30.56 K as depicted in the R–T curve. It also has approximately 40% Jc value of the parent 30-filament wire, at 4.2 K in 3 T.